2010
DOI: 10.1002/ab.20379
|View full text |Cite
|
Sign up to set email alerts
|

The development of the Social Bullying Involvement Scales

Abstract: This study reports findings of a newly developed measure of social bullying based on Underwood's [2003] framework of social aggression. The Social Bullying Involvement Scales (SBIS) consist of four scales measuring the extent to which children experience social victimization, engage in social bullying, witness social bullying, and intervene in social bullying. The sample consisted of 636 participants (311 females and 325 males, age range 11-16 years; 71% White). Confirmatory factor analysis supported a revised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 85 publications
(146 reference statements)
1
42
0
5
Order By: Relevance
“…A CFA showed that after accounting for sample size, indices indicated acceptable levels of overall fit. Although measures were lower than ‘ideal’ thresholds, they were consistent with comparable tools measuring similar domains (Fitzpatrick and Bussey, ; Koomen et al., ; Koster et al., ; Tarshis and Huffman, ) (this is especially true given the heterogeneity of the sample under investigation – see strengths and limitations). Despite this high level of variation within the sample, there was also invariance of model fit across the broad categories of SEND (BESD, cognition and learning, communication and interaction, and sensory and/or physical difficulties).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…A CFA showed that after accounting for sample size, indices indicated acceptable levels of overall fit. Although measures were lower than ‘ideal’ thresholds, they were consistent with comparable tools measuring similar domains (Fitzpatrick and Bussey, ; Koomen et al., ; Koster et al., ; Tarshis and Huffman, ) (this is especially true given the heterogeneity of the sample under investigation – see strengths and limitations). Despite this high level of variation within the sample, there was also invariance of model fit across the broad categories of SEND (BESD, cognition and learning, communication and interaction, and sensory and/or physical difficulties).…”
Section: Discussionsupporting
confidence: 66%
“…For the current study, chi‐square was supplemented with the comparative fit index (CFI), the Tucker–Lewis coefficient (TLI), root mean square residual (RMR) and root mean square error of approximation (RMSEA). Ideal fit indices were created by examining the indices reported in a range of similar inventories in order to estimate what is considered ‘good fit’ in the measurement of psychosocial outcomes (Fitzpatrick and Bussey, ; Georgiou, ; Hatami, Motamed and Ashrafzadeh, ; Kim and Kamphaus, ; Ryser, Campbell and Miller, ). The results of the CFAs are shown in Table and represented graphically in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The associations of RA with anxiety versus with depression were compared. This included studies that focused only on anxiety or depression, and four studies that provided separate correlations for anxiety and depression contributed an ES to each group (Fitzpatrick & Bussey, 2011;McNeill, 2001;Potter, 2009;Pullataz et al, 2007). The mean ES (k = 10) for the association with anxiety (r = .22, SD = .13) was significantly higher than the association (k = 19) with depression (r = .19, SD = .14), X 2 (1) = 4.01, p = .05.…”
Section: Moderator Analysesmentioning
confidence: 99%
“…Kawabata and Crick (2013) found a significant difference in the correlations of European American children (r = .16, ns) and Asian American children (r = .37, p < .05). Recognizing that country of residence is not the same as ethnicity, the international studies found correlations of .25 and .12 in Australia (Fitzpatrick & Bussey, 2011;Zimmer-Gembeck, Hunter, &Prock, 2007), .13, .33, and.25 in Canada (Leenaars, et al, 2008;Onyskiw, 1999), .28 and .38 in Japan (Kawabata et al, 2010a;Kawabata et al, 2010b), and .06 in Russia (Kholodova, 2011). The average correlation in these studies (r = .23) is almost identical to that of the U.S. studies.…”
Section: Moderator Analysesmentioning
confidence: 99%
“…Researchers who have assessed victimization separately from the perspective of the target and perpetrator have used the term peer victimization to denote experiences as a target of victimization and peer bullying to denote propensity to engage in victimization (e.g., Espelage & Holt, 2001;Fitzpatrick & Bussey, 2011;Parada, 2000). Consequently, the present study used the term peer victimization to denote adolescents' experiences as a target of peer victimization and peer bullying to denote adolescents' experiences as a perpetrator of peer victimization.…”
mentioning
confidence: 99%